Pendampingan Gerak Dasar Tari Tradisional Bagi Guru dalam Penguatan Karakter Pelajar Pancasila di Sekolah Dasar Ta’allumul Huda Bumiayu - Noviea Varahdilah Sandi; Cintya Nurika Irma; Fita Dwi Oktavia; Dian Mike Rohmah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Current developments greatly influence human behavior, especially elementary school children. In order for elementary school students to remain focused on positive rules, of course there needs to be good, directed and targeted provision with the aim that elementary school children can grow into students who obey the rules. Teachers provide knowledge of traditional arts to students so that students can know and preserve traditional arts culture, with the other aim of ensuring that traditional dances do not fade with the times amidst the current onslaught of modern dances. Of course, it is not an easy matter for teachers to carry out achievement targets in preserving traditional culture for students. The task of teachers and parents is clearly needed so that children do not fall into negative things, especially in the school environment. Looking at the aspect of the dance environment at Ta'allumul Huda Elementary School by strengthening the character of Pancasila students, it is necessary to provide provision, training and assistance to teachers, grades 4, 5 and 6, by providing traditional dance material and also assistance with basic traditional dance techniques. Central Java. The result of this service activity is that all class teachers can understand aspects of traditional dance by strengthening the character of Pancasila students, and teachers can learn the movements and names of basic Central Javanese traditional dance movements, and teachers can practice basic dance movements through Banyumasan dance.